Macrofinancial Stress Testing : Principles and Practices-Background Material. (Policy Papers; Policy Paper ;, 2012)
Staff conducted a survey of stress testing practices among selected national central banks and supervisory authorities. The online survey was undertaken in November 2011 as part of the preparatory work for the paper on ?Macrofinancial Stress Testing: Principles and Practices. The survey focused on stress testing for banks, which is more widespread and better established-and practices are therefore easier to compare across countries-but also included questions on stress testing for nonbank financial institutions.